FOXP3, a selective marker for a subset of adult T-cell leukaemia/lymphoma. - Roncador, G; Garcia, J; Garcia, J; Maestre, L; Lucas, E; Menarguez, J; Ohshima, K; Nakamura, S; Banham, A; Piris, M (2005)
FOXP3 is a forkhead transcription factor family member, implicated in T-cell regulation, activation and differentiation. FOXP3 has been shown to be a master control gene for the development and function of CD4+/CD25+ regulatory T-cells (T(reg)). In this study, FOXP3 protein expression has been analysed using a new anti-FOXP3 monoclonal antibody in 172 paraffin-embedded lymphoma samples. FOXP3 expression in tumour cells was confined to adult T-cell leukaemia/lymphoma (ATLL) cases (17/25, 68%), with some variability in the intensity of the staining and the proportion of positive cells. No other lymphoma types studied exhibited FOXP3 expression in the malignant population. The selective expression of FOXP3 by tumour cells in ATLL makes this antibody a potentially useful diagnostic tool.